Anti-Toxoplasmic Immunoglobulin G Quantitation Correlates with Immunovirological Parameters of HIV-Infected Cameroonians - Ka’e, Aude C.; Sosso, Samuel Martin; Fokam, Joseph; Simo, Rachel Kamgaing; Essama, Sara Riwom; Nka, Alex Durand; Yagai, Bouba; Dzukou, Cédric Joël Ninsu; Tchouaket, Michel C. T.; Chenwi, Collins; Abba, Aissatou; Fainguem, Nadine; et al. (Current HIV Research, 2021)
Background: Toxoplasmosis is still a neglected common opportunistic infection in immunocompromised individuals, who are mainly people living with HIV (PLHIV) in whom reactivation of toxoplasmosis may occur with advanced HIV conditions in resource-limited settings (RLS). Objective: The objective was to assess the correlation between anti-toxoplasmic immunoglobulin G (anti-Toxo IgG) concentration and the immuno-virological status of PLHIV. Methods: A cross-sectional study was conducted in the year 2018 among 100 PLHIV aged ≥18 years in Yaounde-Cameroon. For each participant, anti-Toxo IgG, CD4-T lymphocytes, and plasma viral load (PVL) were measured using ELISA, flow cytometry, and real-time PCR, respectively. Results: Overall, 56% of the participants were seropositive for anti-Toxo IgG, while 33% were negative and 11% were equivocal. All (n=19) those with PVL>1000 copies/mL were seropositive to anti-Toxo IgG versus 52.85% (37/70) with PVL<1000 copies/mL; p<0.0001. Interestingly, all (n=11) those with severe immunodeficiency (T-CD4<200 cells/μL) were positive to anti-Toxo IgG versus 57.69% (45/78) with T-CD4>200 cells/μL; p<0.0001. Most importantly, PVL and anti- Toxo IgG concentration were positively correlated (r = 0.54; p<0.0001), while T-CD4 and anti- Toxo IgG concentration were negatively correlated (r = - 0.70; p<0.0001). Adjusting age, gender, immune status, and virological profile in logistic regression shows that only immune status was independently associated with the serological status of toxoplasmosis (p=0.0004). Conclusion: In Cameroon, about half of PLHIV might be seropositive to anti-Toxo IgG, with decreasing immunity appearing as a risk of toxoplasmosis relapse. Thus, in the context of immunodeficiency, routine quantification of anti-Toxo IgG would alleviate the programmatic burden of this opportunistic infection in RLS with the generalized HIV epidemic.
Keywords: immunity